(untitled) (Ágora de Heterodoxias, 2021)
This essay analyzes the constitutionality and legality of the measures implemented by numerous municipalities -communal administration organism- in Chile, in March 2020, to face the health crisis caused by Covid-19, thus trying to avoid and/or reduce contagions among its inhabitants. These actions have implied an impact on the fundamental rights of people, such as freedom of movement, freedom of worship, the right of assembly and the free exercise of economic activities, which in accordance with the Political Constitution of the Republic of Chile can only be carried out by legal means, being an attribution of the Legislative Power.